Cancer‐testis antigen MAGEC2 promotes proliferation and resistance to apoptosis in Multiple Myeloma. (12th October 2015) - Lajmi, Nesrine; Luetkens, Tim; Yousef, Sara; Templin, Julia; Cao, Yanran; Hildebrandt, York; Bartels, Katrin; Kröger, Nicolaus; Atanackovic, Djordje
Summary: Cancer‐testis antigens belonging to the MAGE family of genes, such as MAGEC2, are commonly and specifically expressed in Multiple Myeloma (MM) and are associated with a more aggressive clinical course and chemotherapy resistance. MAGEC2 is thought to be an excellent candidate for cancer immunotherapy; however, the biological role of MAGEC2 in MM has remained unclear. We investigated the biological role of MAGEC2 in myeloma cells determining the effect of MAGEC2 knockdown on proliferation and apoptosis. Loss of MAGEC2 resulted in reduced proliferation, viability, and anchorage‐independent growth of myeloma cells irrespective of the functional status of TP53 (p53). The anti‐proliferative effect of MAGEC2 silencing was due to a decrease of cells in the S phase, cell cycle delay at both G0/G1 and/or G2/M, and an increase in the sub‐G0/G1 diploid population related to apoptotic cell death. Importantly, overexpression of short hairpin (sh)RNA‐refractory MAGEC2 rescued the anti‐proliferative effect of mRNA knockdown and protected cells from apoptotic cell death. Our findings support a TP53‐independent role of MAGEC2 in promoting the survival of myeloma cells suggesting that MAGEC2‐specific immunotherapies have the potential to eradicate the most malignant cells within the myeloma tumour bulk leading to durable clinical responses.